PERHITUNGAN POTENSI AIRTANAH DI KAWASAN KAMPUS UNPAD JATINANGOR DENGAN METODE NUMERIK - Barkah, M. Nursiyam; Setiadi, Djajang Jedi; Hadian, Moh. Sapari Dwi (Fakultas Teknik Geologi Universitas Padjadjaran, 2015)
Geological conditions Jatinangor campus is a volcanic deposits that have 3 potential aquifer, the unconfined aquifer is a depth of 0-60 m, confined aquifer 1 at a depth of 80-90 m and confined aquifer 2 at a depth of 120-200 m. The results of groundwater potential calculation is done using the method of numerical groundwater flow pattern is obtained relative trending Northwest - Southeast tend to follow topographical pattern. This is consistent with the geological-geophysical mapping data that the geometry and pattern of shallow groundwater aquifers configuration follows the pattern of topographic contours. However, the groundwater in the aquifer geometry and pattern configuration does unfollow the pattern of topographic contours, but follows the pattern of the stratigraphy and structural geology. The quality of groundwater in the shallow aquifer or aquifer in not affected by topography, groundwater quality is controlled by the pattern of stratigraphic and structural geology. Ground water Chemical typehas results are Ca-HCO3; Mg ; Mg-HCO3 and No-type. The results of measurements of physical character in the field, existing groundwater generally meet the requirements of the quality standards for drinking water. The test results of the pumping test wells 10 point values obtained transmissivity (T) ranged from 86.4 to 467.9 m2 / day and Permeability (K) ranging between 1.2 x 10-4 - 6.3 x 10-6 cm / sec. Based on the well test results obtained transmissivity values diversity and rock permeability significantly, it could be interpreted that the distribution of the research areas of uneven rocks.